A pesar de la muralla y los libros (2015)
This text analyzes the interpretation of history and politics in the essay “The Wall and the Books” by Jorge Luis Borges. From a historical fact, Borges begins a disquisition with a methodology very close to the Nietzschean interpretación of history and his genealogial aproach, contained in more recent years by Michel Foucault. This trial by Borges is not a historical experiment, but an aesthetic and politic exercise that connects it to the contemporary proposal of Jacques Rancière in the aesthetic regime of the arts. The trial results in a proposal to intuit, configure and know reality from an aesthetic point of view.